Integrating technostress creators and inhibitors in using accounting information system to improve job satisfaction and task performance - Mohammed Umar Saganuwan, 1965- author; Wan Khairuzzaman Wan Ismail, supervisor; Ungku Norulkamar Ungku Ahmad, 1968- supervisor; Sekolah Perniagaan Antarabangsa (2015)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2015